2014
DOI: 10.1093/cid/ciu602
|View full text |Cite
|
Sign up to set email alerts
|

Effects of HIV Antiretroviral Therapy on Sexual and Injecting Risk-Taking Behavior: A Systematic Review and Meta-analysis

Abstract: Despite concerns that use of ART might increase sexual or injecting risk-taking, available research suggests that unprotected sex is reduced among HIV-infected individuals on treatment. The reasons for this are not yet clear, although self-selection and mutually reinforcing effects of HIV treatment and prevention messages among people on ART are likely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 106 publications
(79 reference statements)
2
26
1
Order By: Relevance
“…STI prevalence was greatest at the time of HIV diagnosis, and the prevalence of STIs among people receiving ART (16.2%, SD 23.7) was not appreciably different compared to HIV-infected persons not yet on ART (16.5% SD 13.3; p=0.09). A more recent meta-analysis of 55 studies on the effect of ART on sexual risk behaviors and STIs found that sexual risk taking was lower among those receiving ART compared with those not on ART (OR=0.7; 95% CI=0.62–0.81) and that incidence of STIs was also lower among those on ART (OR=0.38; 95%CI=0.33–1.01) [10]. …”
Section: Introductionmentioning
confidence: 99%
“…STI prevalence was greatest at the time of HIV diagnosis, and the prevalence of STIs among people receiving ART (16.2%, SD 23.7) was not appreciably different compared to HIV-infected persons not yet on ART (16.5% SD 13.3; p=0.09). A more recent meta-analysis of 55 studies on the effect of ART on sexual risk behaviors and STIs found that sexual risk taking was lower among those receiving ART compared with those not on ART (OR=0.7; 95% CI=0.62–0.81) and that incidence of STIs was also lower among those on ART (OR=0.38; 95%CI=0.33–1.01) [10]. …”
Section: Introductionmentioning
confidence: 99%
“…ART use was associated with a reduction in unprotected sex (OR 0.55; 95% CI: 0.30–0.99; p<0.001) but heterogeneity was significant (I 2 =85.2%). In another meta-analysis (9), ART use was associated with decreased unprotected sex with HIV-uninfected or unknown status partners (OR 0.64: 95% CI: 0.46–0.88, p<0.001; heterogeneity I 2 =61%). Condomless sex decreases after ART initiation in most populations (9), but some sub-populations experience increased condomless sex over time (25, 26).…”
Section: Discussionmentioning
confidence: 98%
“…In another meta-analysis (9), ART use was associated with decreased unprotected sex with HIV-uninfected or unknown status partners (OR 0.64: 95% CI: 0.46–0.88, p<0.001; heterogeneity I 2 =61%). Condomless sex decreases after ART initiation in most populations (9), but some sub-populations experience increased condomless sex over time (25, 26). A study from Uganda reported decreased sexual risk behavior in women (OR 0.85 per year of ART) but not men (OR 1.41 per year of ART) (23).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In a meta-analysis of 60 studies, injecting risk-taking (measured by sharing needles/syringes) and sexual risk-taking (measured by inconsistent condom use and new sexually transmitted infection diagnoses) were not associated with commencement of HIV antiretroviral therapy [53]. Moreover, among those individuals on therapy, sexual risk-taking was marginally lower, reflecting that individuals commencing long-term therapy are probably self-selecting and lower risk-takers than those not undertaking therapy.…”
Section: Insights From Human Immunodeficiency Virus (Hiv) Infection -mentioning
confidence: 99%